ChemInform Abstract: Efficient Deoxygenation Methodologies Catalyzed by Oxo‐Molybdenum and Oxo‐Rhenium Complexes. Issue 48 (December 2015) - Sousa, Sara C. A.; Fernandes, Ana C.
Abstract: Review: 80 refs.